The Effect of Remuneration and Work Motivation on Work Discipline and Performance of Notary Office Employees - Muqoddas, Ahmad (International Journal of Advanced Multidisciplinary, 2023)
The Effect of Remuneration and Work Motivation on Work Discipline and Performance of Notary Office Employees is a study that is within the scope of the HR Management space (Human Resources), aims to determine whether remuneration and work motivation affect work discipline and performance of notary office employees. The variables used consist of 4 (four) variables, namely the effect of remuneration (X1) work motivation (X2) which is an independent variable and work discipline (Y1) and employee performance (Y2) which is the dependent variable. Data collection methods include interviews and observations After the data is summarized, it is presented and conclusions are drawn. Using two types of data sources: secondary and primary. Methods such as interviews and observations are used to collect data. Presentation and drawing conclusions follow the summary of the facts.